A GUIDE FOR INTEGRATING TOTAL QUALITY MANAGEMENT AND PHYSICAL ASSET MANAGEMENT IN THE FOOD INDUSTRY - Van Heerden, Milandi A; Jooste, Johannes (The South African Journal of Industrial Engineering, 2018)
The integration of an organisation’s asset management and total quality management systems has become important in addressing operational challenges in the food industry. This paper proposes a guideline for implementing these systems through an integrated approach that aims to improve product quality. The grounded theory methodology is used to develop a theory based on expert opinions in the South African food and engineering industries. The results are presented in a model in which systems integration is identified as the central phenomenon for improving food quality. Analysis and interpretation of the model is presented in the form of a guideline for managers.